Pulmonary arterial thromboses and gall bladder wall oedema in a cat with bronchioloalveolar carcinoma. Issue 1 (10th December 2021) - Fortuna, Luca; Yaffy, Dylan; Priestnall, Simon L.; Cook, Simon
Abstract: An 11‐year‐old male neutered British Shorthair cat presented with acute collapse, dyspnoea and paraparesis. Left atrial enlargement and left‐sided congestive heart failure were excluded by point‐of‐care ultrasonography, and gall bladder wall oedema was detected. Comparative venous blood gas analyses confirmed ischaemia of the hindlimbs, and echocardiography was consistent with pulmonary hypertension. The patient was euthanased and a postmortem examination revealed pulmonary artery thromboses associated with bronchioloalveolar carcinoma.